APPLICATION OF CRISPR ACTIVATION (CRISPRa) SYSTEM TO ZEBRAFISH (Danio rerio) GENES - Rizka Rahmana Putri (JURNAL MINA SAINS, 2019)
CRISPR activation system is part of the function of CRSPR/Cas9 which is used to manipulate certain genes by activating these genes. CRISPR activation utilizes dCas9 (dead-Cas9) or Cas9 which is deactivated as DNA scissors, so that the use of Cas9 for gene activation does not cause targeted DNA chain termination. This research that uses this CRISPR activation is applied to the zebrafish gene (Danio rerio) aims to determine the mRNA level of the targeted gene. In this study, the ASCL1a and BCL6a genes from zebrafish were targeted as the object of study. The results showed that genes from zebrafish that were targeted had an increase in mRNA levels after being activated using CRISPR activation system. Keywords: CRISPR activation system (CRISPRa), zebrafish (Danio rerio), dCas9, ASCL1a gene, BCL6a gene